Sustainable Entrepreneurship Practices In Malaysian Manufacturing Smes: The Individual, Organisational And Institutional Impacts - Khairul, Noor Liyana; Rajendran, Afendi (2017)
The research framework for this study is built upon the triple bottom line agenda. Specifically, the study integrates the individual factor that consist of sustainable orientation, organisational factor that consists of intellectual capital (human, structural and relational capital) and institutional factors that consist of government support and social norms as the antecedents of sustainable entrepreneurship practices, whereas sustainable performance of SMEs is treated as the dependent variable. The theories used to link all the antecedents and independent variable is Resource-Based View (RBV), Upper Echelons Theory (UET) and Institutional theory.